Going to the Clay: Exploring Conflicts and Values of the Soil in Valparaíso - Salgado Cofré, Daniela; Mercado Jara, Álvaro (Revista GEMInIS, 2022)
This proposition presents a design and artistic research focused on the soil and aimed at generating active and poetic forms of reflection around the fragile interdependence of human and non-human lives in an increasingly precarious urban environment, emphasised by the current ecological crisis. In order to engage in such reflections, this practice-oriented research —led by designers, architects, artists and educators— explored and expected to make visible the transformation of peripheral urban areas of the Region of Valparaíso, in Chile. To do so, we focused on following the uses of the soil, identifying conflicts and values that emerge around these extraction sites through immersive sensitive experiences. These collective experiences titled ‘Going to the Clay’ had the objective of searching for clay pits in different sites as the means to establish sensitive connections with the soil and its matter. Thus, the sum of collective and creative explorations performed in the veins and clay pits of Valparaíso served to trace other relational ways of inhabiting, valuing, and working with the soil. We envisage this practice-oriented research project as a poetic alternative to critically question the modern technocratic logics of urbanisation that operate in the region through the commodification and overexploitation of the land.